(Re)arrangements of a “utopia of a national sound”: bossa nova as the realization of a modern musical project of Mario de Andrade (Tempo e Argumento, 2009)
This text aims to argument about the historic relation between Mário de Andrade’s project to Brazilian music (his “national sound utopia”, as Arnaldo Contier called it) and one of its possible realization with bossa nova. The text presents in general lines the Andradian project, its committed character, its incursions in the problems of “popular” and “erudite” and its filiations to the national obsession with “formation”. It exposes punctually the possible comprehension of bossa nova as a modernist project, suggesting a logicality of continuity in Brazilian musical experience.
Keywords: Mário de Andrade; bossa nova; brazilian musical experience